Functional materials : an introduction with worked examples / Haixue Yan, Harshad K.D.H. Bhadeshia. - Yan, Haixue; Bhadeshia, H. K. D. H. (Harshad Kumar Dharamshi Hansraj), 1953- ([publisher not identified], 2025)
Functional materials represent those specifically designed to exhibit unique and often tuneable physical or chemical properties in response to external stimuli. They are valued for their 'function' - their ability to perform a specific task or change their behaviour under certain conditions. They can change their shape, electrical conductivity, magnetic properties, colour, or other characteristics when exposed to temperature, pressure, electric fields, magnetic fields, light, or chemical changes. This short book serves as an introduction, providing sufficient and complete coverage of concepts suitable for a final year undergraduate course.